Are South Africa's section 23m interest limitation rules sufficiently targeted and effective in combatting base erosion and profit shifting through earnings stripping schemes by associated enterprises? - Gwaambuka, Tatenda (Department of Commercial Law, 2023)
Earnings stripping is a simple structure whereby one affiliate company resident in a low or no tax jurisdiction advances an intra-group loan to another affiliate member company resident in a high tax jurisdiction so that the latter makes excessive deductible interest payments. The overall effect of the structure is to move profits from a high tax jurisdiction through the interest payments to a low tax jurisdiction and thus reduce the multinational group's effective tax rate. This study focuses on how such a structure can arise in the South African tax system and if the measures in section 23M are sufficiently targeted and effective to address the problem without affecting legitimate corporate financing decisions. Considering that South Africa is a medium to high tax jurisdiction, the study focuses on those structures in which the borrower is resident in South Africa and the lender is resident in a low or no tax jurisdiction. To achieve these objectives, the study outlines how earnings stripping schemes arise in the South African context, finding that two conditions should simultaneously exist: a deduction/exemption mismatch in South Africa and low or no foreign taxation on interest in the lender's jurisdiction of residence. The study also finds that on an analysis of the normal and withholding tax systems in South Africa, a deduction/exemption mismatch can only arise from the operation of treaty law limits on South African taxing rights. This means problematic, tax motivated earnings stripping schemes which take advantage of the deduction/exemption mismatch arise from treaty abuse. This reformulation of the problem as being treaty-based informs this study's analysis of whether section 23M is sufficiently effective and targeted. The study finds that because of its domestic focus, section 23M is neither sufficiently effective nor specific in addressing earnings stripping schemes. The author, therefore, proposes a radical shift in how South Africa deals with earnings stripping schemes: amending section 23M to account for the foreign tax treatment of interest and reframing the rule as a provisional measure while South Africa focuses its long-term efforts on treaty-based reforms.